Rancang Bangun Aplikasi Augmented Reality Pengelolaan Rambu-Rambu Lalu Lintas Menggunakan Global Positioning System (GPS) pada Android - Mohammad Fatoni Anggris; Mahardeka Tri Ananta; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The traffic signs are a symbol of traffic order useful as warning, prohibition, command and directions. The management signs by the division of Rekayasa Lalu Lintas (RLL) get some obstacles in collecting data that have been installed. Data collection which done by the officers still using manual guide. Every survey have been conducted by surveyor, returned to office for result and need long time. Meanwhile, field officers also get some problems in determining route and position of signs that will be installed. The solution to simplify sign management is to build an integrated system between mobile application and web application. Web application which as server is a web service based to process exchanging sign data. Mobile application as client by doing CRUD process and based AR and GPS to facilitate installation positioning signs. The result of application is able to perform the process of signs management well. Result of validation test results have occupied functional requirements and result of usability testing obtained 79.5 SUS score from field officer and 80.5 SUS score from surveyor. Meanwhile results of compatibility testing get 100% valid results and result of GPS accuracy approach testing obtained highest result is 4.039m and lowest is 1.812m.